Women's Roles in Women's Poverty in Eight Industrialized Countries - Annemette Sorensen; Lynne Casper; Sara McLanahan (Luxembourg Income Study (LIS), 1992)
This paper examines women's roles and economic status in eight industrialized countries, using data from the LIS in an established welfare state topology framework. The two part analysis compares the variation in women's roles across countries, as well as the relationship between role and economic status in different countries.
Keywords: 330